The Microanatomy Of The Human Skin: Understanding The Structure-Function Relationship In Barrier Function And Immune Defense (Journal of Pharmaceutical Negative Results, 2022)
Background: the human skin is the body’s first line of defense against pathogens and, at the same time, regulates the organisms internal environment. To be able to appreciate its functions in barrier and immune functions, it is quite important to comprehend the skin at the microanatomical level.Objectives: In this research work, the study of mammalian skin, topology and its functions at the micro scale in barrier and immune defense will be of interest.Study design: A Cross-sectional studyPalce and duration of study. Watim Medical & dental college rawat from jan 2020 july 2020Methods: Skin biopsies were made from 150 patients, and the samples were examined by using histological methods. Thickness of epidermal layers, immune cells infiltration and lipid content were determined. . These variables were compared with skin barrier function using statistical toolkit to determine if there is the existence of any relationship.Results: The correlation was confirmed between the stratum corneum thickness and barrier function with 68 % enhancement in barrier function for the increased thickness(r = 0. 68, SD = 0. 12, p < 0. 01. Furthermore, increased lipids density in the SC was related to decrease of TEWL by 45% (SD = 0. 15, p < 0. 05). Correlation of Langerhans cell density and immune responsiveness showed that density has a significant relationship with an increased general responsiveness that is 72 percent higher on average (r = 0. 72 SD = 0. 10, p < 0. 01).Conclusion: Skin barrier function is chiefly attributed to the outer most layer of epidermis, the stratum corneum and immunoelectromicroscopic study shows that Langerhans cells are involved in skin defense. Thus, these results call for additional investigation of potential strategies to improve skin barrier function.